Profesor Stanisław Borowski jako historyk gospodarczy - Rusiński, Władysław (Wydział Prawa i Administracji UAM, 1981)
Professor Stanisław Borowski, though professionally connected with statistics and demography, stalled his economic activity with research on economic and social history. As a participant of a seminar conducted by Prof. Jan Rutkowski, who was one of co-originators of the science of economic history in Poland, he earned first knowledge on research methods of economic historian. First of all, he learned to- esteem and use in practice principles of closeness and reliability in all scientific undertakings. He stayed true to the principles until the end of this life. After Prof. Rutkowski's death (1949) Stanisław Borowski put forth further scientific activity under direction of the author. The protection turned into a sincere, obliging friendship later on. Scientific output of Professor Borowski is impressive in the scope of economic history. It is mainly devoted to the history of Wielkopolska agriculture and country in the 19th and the 20th centuries. It comprises a few voluminous monographic works, f. ex. a great monographs entitled „Genesis and Labour Conditions of Agrarian Workers in Wielkopolska During Great Agrarian Reforms (1816 - 1860)", the work qualifying for assistant-professorship entitled „Stratification of Wielkopolska Country in the Years 1807 - 1914", numerous minor treatises and articles, methodic studies, papers prepared for scientific congresses and conferences (in which Prof. Borowski participated intensely) and critics of Polish and foreign publications in the scope of economic and social history. All Prof. Borowski's works are based on very profound source data. Owing to wide utilization of statistical methods and stress put on research on social structures they liken the trend represented by the French „histoire quantitative" Unusual dilligence of Professor Borowski won over the common respect for him. The premature death, unfortunately, put an end to his further scientific plans. His voluminous output, however, in the scope of economic history has remained. It occupies a very important place in Polish historiography.
Professor Stanisław Borowski as an Economics Historian